Comparison of intrathecal bupivacaine with or without fentanyl for urosurgeries - Shrestha, Bibhush; Acharya, Subhash Prasad; Roshana, Amatya (Journal of Society of Anesthesiologists of Nepal, 2015)
Introduction: Spinal anaesthesia has been widely used for urological operations because it permits early recognition of symptoms caused by overhydration, transurethral resection of prostate syndrome and bladder perforation. Short acting spinal anaesthesia may help to prevent complications associated with delayed immobilization. Our study was undertaken to examine whether adding 25?g fentanyl to bupivacaine would intensify sensory and motor block without prolonging recovery time. Materials and Methods: Ninety American Society of Anaesthesiologists physical status I and II scheduled for elective urological procedures were studied in a double-blinded, randomized prospective manner. Random allocation was done as , Group I (n=30) receiving intrathecal bupivacaine 12.5 mg; Group II (n=30) bupivacaine 10 mg with 25 ?g of fentanyl; and Group III (n=30), bupivacaine 5 mg with 25 ?g of fentanyl. Assessment of sensory, motor block and duration of sensory analgesia was done. Result: There was statistically significant difference regarding total duration of motor block, time for two-segment regression and duration of sensory analgesia between each pair of groups. The duration of motor block, time for two segment regression and duration of sensory analgesia was found to be longest in Group II and shortest in Group III. There were no significant differences in the incidence of complications. Conclusion: Addition of 25 ?g fentanyl to 5 mg bupivacaine resulted in short-acting motor block whereas with 10 mg of bupivacaine, it increased the intensity and duration of motor block, prolonged sensory analgesia and two segment regression time. Journal of Society of Anesthesiologists 2014 1(1): 18-21